Pengaruh Penggunaan Media Gim Edukasi terhadap Hasil Belajar Matematika Siswa Kelas VII MTs Ra’iyatul Husnan (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This study aims to determine the effect of using educational gim-based learning media on students' math learning outcomes on the material of Linear Equation One Variable (PLSV). The background of this research is the low student learning outcomes in conventional math learning which is considered less interesting, especially in PLSV material which is abstract. This study used a quantitative approach with a quasi-experimental design and a nonequivalent control group design. The sample consisted of two classes, namely the experimental class (using educational gim media) and the control class (using conventional methods), which were taken from VII grade students of MTs Ra’iyatul Husnan, Wringin Bondowoso. The research instrument was in the form of pretest and posttest tests that had gone through validity and reliability tests. The pretest results showed that both classes had relatively balanced initial abilities. However, in the posttest, the learning outcomes of experimental class students showed a more significant increase than the control class. The data were analyzed using normality, homogeneity, and Mann-Whitney U Test hypothesis tests because the posttest data were not normally distributed. The analysis results showed a significance value of Asymp. Sig. (2-tailed) significance value of 0.000 <0.05, which means there is a significant effect of using educational gim media on student learning outcomes. This finding shows that interesting and interactive learning media such as educational gims can improve students' motivation, understanding and learning outcomes in mathematics. Therefore, the use of educational gims is recommended as an innovative alternative in learning mathematics, especially on material that is abstract and difficult for students to understand.